Identidades : interface entre religião e negritude - Pacheco, Lwdmila Constant (2010)
This work aims to establish the relationship between religious belonging and blackness. To this, we conducted individual interviews with two distinct religious groups: six people in the Universal Church of the Kingdom of God and six people of Candomblé. We questioned about the racial and religious belonging. We conducted a qualitative analysis in which we compared the answers given by respondents who, besides being divided into different religious groups were also categorized into three subgroups of generations. In groups generational people are divided by time of accession to religion. It is intended that the proposed subdivision understand how much time within the religion influences the racial and religious discourse. Used as comparison criteria to categorize the people described in the three generations - First generation, second and third. A generational comparison was made within the same religious group and between groups. The results indicate that the discourses related to religious belonging in candomblecistas differ qualitatively as well as blackness and racial consciousness. People with more time in Candomblé tend to say black or african descent belonging to a religious context that encourages such biological and cultural heritage, as people with little time for inclusion in Candomblé not expressed to feel part of african-descent. In the case of the Universal Church, we do not perceive significant differences between the discourses inter-generational, but compared to Candomblé, we found that there was none of those interviewed in the affirmation of blackness, however there were some statements that denounce the rejection of the cults of African origin, which denotes a sense of not belonging to African. Thus, depending on the religious group membership, there is a favoring or disfavoring of blackness, which enhances the more time to join the religious group participant has.